IMPROVING THE STUDENTS’ ENGLISH LISTENING ACHIEVEMENT THROUGH DICTATION AS AN INSTRUCTIONAL DEVICE AT SMP NEGERI 1 MAKASSAR - tenri ugi irianto (UKI TORAJA, 2015)
This research aims at finding out whether the use dictation through instructional device can improve students’ English listening achievement. This research employs quasiexperimental method which consists of two groups namely experimental and control group. Each group consists of 32 students. The sample is chosen by applying cluster random sampling technique. The instruments of this research are listening test and questionnaire.The data of this research is collected through pre-test and post-test. Pre-test is applied to find out the students’ ability before and after treatment. In conducted of this research, the researcher applied dictation as an instructional device. The result of data analysis on pretest and post-test shows that T-test result is 13.03 and T-table is 2.00 which indicated the students’ improvement. Based on the result of research, it can be assumed that the use of dictation can improve students’ listening achievement.